PENGAMBILALIHAN OBYEK JAMINAN HAK TANGGUNGAN DALAM HAL KREDIT MACET PADA PT. BANK MANDIRI (PERSERO) TBK CABANG JAMBI - , TRIAMY ROSTARUM ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to find out when the object of mortgage guarantee which belong to debtor who suffered non-performing loan can be acquisired by PT. Bank mandiri (Persero) Tbk Jambi Branch, and to identify the role of Land Certificate Officer (PPAT) in making deed for the guarantee in which acquisired by PT. Bank mandiri (Persero) Tbk Jambi Branch. This research use empirical juridical method, which is by doing research in order to collect primary data related to field research and also supported with library research to collect secondary data. The library research obtained from reading and learning from literature and relevant researches, whereas field research obtained through interview with interviewees and respondents. The result of research and discussion i.e. after executing the mortgage guarantee through auction and the guarantee is unsold, then PT. Bank mandiri (Persero) Tbk Jambi Branch can conduct acquisition the mortgage guarantee, known as AYDA through auction by signing mortgage acquisition agreement between bank and debtor or by preparing an official report about credit settlement which is be notarized, afterward proceed with making Acte de Command i.e. statements between buyer designated by bank (usually a bank employee) and debtor whose contents is that the buyer in act of buying the mortgage which done for the benefit of other party whose name will be specified later and appointed to replace the buyer. Purchased mortgage object must be sold at the latest of 1 year. The role of Land Certificate Officer (PPAT) is to make selling-purchasing deed (AJB) which becomes the legal rights for transferring the land right in acquisition of debtorâs mortgage guarantee.